Encyclopedia of social networks - Barnett, George A.; SAGE Knowledge (Online service). (Los Angeles, Calif. Sage, 2011)
"This two-volume encyclopedia provides a thorough introduction to the wide-ranging, fast-developing field of social networking, a much-needed resource at a time when new social networks or "communities" seem to spring up on the internet every day. Social networks, or groupings of individuals tied by one or more specific types of interests or interdependencies ranging from likes and dislikes, or disease transmission to the "old boy" network or overlapping circles of friends, have been in existence for longer than services such as Facebook or YouTube; analysis of these networks emphasizes the relationships within the network . This reference resource offers comprehensive coverage of the theory and research within the social sciences that has sprung from the analysis of such groupings, with accompanying definitions, measures, and research.Featuring approximately 350 signed entries, along with approximately 40 media clips, organized alphabetically and offering cross-references and suggestions for further readings, this encyclopedia opens with a thematic Reader's Guide in the front that groups related entries by topics. A Chronology offers the reader historical perspective on the study of social networks."-Provided by publisher.
Includes bibliographical references and index.
Keywords: Social networks -- Encyclopedias; Electronic books